Uji Efektivitas Antibakteri Larutan Lo’i Keta dan Ekstrak Methanol Lo’i Keta Terhadap Pertumbuhan Staphyloccus Epidermidis dan Pseudomonas Aeruginosa - Safari, Dilfa Atri; Musyarrafah; Rozikin; Rini, Setio (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to determine the antibacterial activity of Lo’i keta solution and methanol extract against the growth of Staphylococcus epidermidis and Pseudomonas aeruginosa. The research employed a true experimental design using a Posttest Only Control Group Design with the well diffusion method. A total of 80 samples were divided into 20 treatment groups with concentrations of 25%, 50%, 75%, and 100%, along with a positive control (ciprofloxacin) and a negative control (distilled water). GC-MS analysis revealed nine bioactive compounds in the methanol extract of Lo’i keta. The results showed that the Lo’i keta solution inhibited the growth of Staphylococcus epidermidis with inhibition zones ranging from 15–24 mm, while the methanol extract produced larger inhibition zones of 18–32 mm. Against Pseudomonas aeruginosa, only the methanol extract demonstrated antibacterial activity with inhibition zones of 13–17 mm, whereas the solution showed no inhibitory effect. The Kruskal-Wallis test indicated significant differences among the treatment groups. In conclusion, both the Lo’i keta solution and the methanol extract were effective in inhibiting the growth of Staphylococcus epidermidis, while antibacterial activity against Pseudomonas aeruginosa was observed only in the methanol extract. Lo’i keta demonstrates potential to be developed as a traditional medicine-based antibacterial alternative.